2017
DOI: 10.1103/physrevd.96.103524
|View full text |Cite
|
Sign up to set email alerts
|

Natural inflation from polymer quantization

Abstract: We study the polymer quantization of a homogeneous massive scalar field in the early universe using a prescription inequivalent to those previously appearing in the literature. Specifically, we assume a Hilbert space for which the scalar field momentum is well defined but its amplitude is not. This is closer in spirit to the quantization scheme of loop quantum gravity, in which no unique configuration operator exists. We show that in the semi-classical approximation, the main effect of this polymer quantizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Among these, with specific application to cosmology, is one that uses a fixed quantum state to compute the expectation value of the matter Hamiltonian. This "effective" Hamiltonian is then used in the Hamiltonian constraint to derive a modified classical dynamics [14][15][16];…”
Section: The Kasner-schrödinger Equationmentioning
confidence: 99%
“…Among these, with specific application to cosmology, is one that uses a fixed quantum state to compute the expectation value of the matter Hamiltonian. This "effective" Hamiltonian is then used in the Hamiltonian constraint to derive a modified classical dynamics [14][15][16];…”
Section: The Kasner-schrödinger Equationmentioning
confidence: 99%
“…The polymer quantization has been motivated from loop quantum gravity [1,2]. In fact, the polymer quantization of simple matter fields has been studied and the conclusions reached resemble the conclusions obtained in loop quantum gravity [3,4]. It has been demonstrated that the polymer quantization leads to radiation in inertial frames [5], and a modification of black body radiation at high temperatures [6].…”
mentioning
confidence: 92%
“…We start by analyzing the effect polymer quantization would have on the Heisenberg algebra. It is known that in the polymer quantization, the usual phase space (x, p) can be replaced by [3,4] x…”
mentioning
confidence: 99%
See 1 more Smart Citation